2017
DOI: 10.1016/j.ebiom.2017.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Correlates of Virological Failure in Individuals Receiving a WHO-Recommended Tenofovir-Containing First-Line Regimen: An International Collaboration

Abstract: Tenofovir disoproxil fumarate (TDF) genotypic resistance defined by K65R/N and/or K70E/Q/G occurs in 20% to 60% of individuals with virological failure (VF) on a WHO-recommended TDF-containing first-line regimen. However, the full spectrum of reverse transcriptase (RT) mutations selected in individuals with VF on such a regimen is not known. To identify TDF regimen-associated mutations (TRAMs), we compared the proportion of each RT mutation in 2873 individuals with VF on a WHO-recommended first-line TDF-contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 28 publications
3
45
0
1
Order By: Relevance
“…We found that the mutation rate of S68G increased in almost all HIV-1 subtypes in drug-experienced populations, with the greatest increase noted among CRF01_AE strains. This finding is supported by several studies on non-subtype B HIV-1 [17,18]. Based on the available evidence, it is suggested that S68G may be new mutation associated with the development of drug resistance.…”
Section: Discussionmentioning
confidence: 62%
“…We found that the mutation rate of S68G increased in almost all HIV-1 subtypes in drug-experienced populations, with the greatest increase noted among CRF01_AE strains. This finding is supported by several studies on non-subtype B HIV-1 [17,18]. Based on the available evidence, it is suggested that S68G may be new mutation associated with the development of drug resistance.…”
Section: Discussionmentioning
confidence: 62%
“…Moreover, previous studies showed that patients infected with subtype B and non-B subtype HIV-1, who failed ART and developed the K65R mutation, also acquired the S68G mutation [18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…The viral pol gene was amplified and sequenced. The ChromatQuan Internet tool was used to calculate the viral ratio at each time point [16].…”
Section: Growth Competition Assaymentioning
confidence: 99%